Distribution transformers modeling with angular displacement: actual values and per unit analysis - R., Dario E. Rodas; Padilha-Feltrin, Antonio [UNESP]; Ochoa, Luis F. (Sociedade Brasileira de Automática, 2007)
In this work a detailed modeling of three-phase distribution transformers aimed at complementing well-known approaches is presented. Thus, incidence of angular displacement and tapping is taken into account in the proposed models, considering both actual values and per unit. The analysis is based on minimal data requirement: solely short-circuit admittance is needed since three-phase transformers are treated as non-magnetically-coupled single-phase transformers. In order to support the proposed methodology, results obtained through laboratory tests are presented.
Keywords: Transformer modeling; angular displacement; distribution systems